Keterwakilan Etnis di Politik Nasional: Kasus Etnis Sunda di Republik Indonesia - Sujatmiko, Iwan Gardono (Masyarakat: Jurnal Sosiologi, 2014)
The article aims to construct an analytical model to explain why the presence of Sundanese political leaders at the national level is relatively low despite that they are the second largest majority group in Indonesia. The model focuses on historical factor, social network, culture, as well as the role of local government and society. The historical factor is crucial as to describe the importance of Sundanese’s position with Bandung as its core in its sociopolitical relation with Jakarta. The social network explores the connectivity between Sundanese with the national network, while the cultural factor is essential in analyzing the effect of values and behaviour of Sundanese in politics. The model will also include the roles of local government and Sundanese society in supporting the Sundanese to increase the presence of their political leaders at the national level.